Black skin, white masks: Izzat as an appropriation of Othello. Issue 1 (1st August 2021) - Chatterjee, Koel
Izzat was the first mainstream Hindi film to reference Othello and has so far escaped the attention of academics who have begun researching the underexplored field of Bollywood Shakespeares. The film stars Dharmendra playing both versions of a fair- and a dark-skinned twin, which is a novel take on a Shakespearean trope. As a mainstream film, Izzat does not aspire to the pedagogical cultural capital of Shakespeare that Saptapadi does, nor does it reference the performance traditions of Othello onstage or film. However, references to Othello that seem superficial at first glance are embedded throughout the film. The only direct reference to the play is when Deepa meets Shekhar (who is pretending to be his twin Dilip) for the first time, and he sees she has been reading Othello. This sparks off a conversation about appearances and colour prejudices that is quite alien to an industry that traditionally favours light-skinned protagonists but rarely acknowledges it. Through this article, I would like to explore the ways in which Shakespearean tropes, and in particular Shakespeare's Othello, has been used to explore postcolonial anxieties about identity in India by juxtaposing Adivasi identities with more typical urban Indian identities. The film also suggests that the colonizers have been replaced in Indian society by the urban elite who value superficial white masks and practise a racism that is much more insidious by discriminating against other Indians based on colour, caste and class. Through this exploration, I will also examine how Othello impacts the Indian psyche and why the referencing of Othello in this film points towards the many ways in which Othello is adapted and appropriated in Indian mainstream media.